Vida de cientista: um estudo sobre a construção da biografia de Mme Curie (1867-1934) - Tonetto, Sonia Regina (2009)
The object of analysis of this study is the first biography of Madame Curie, written by her daughter Eve Curie. This book portrays the historical period, family life and the rise of the professional scientist. The first chapter reviews the author's intent in building the image of the biographied. The expressions used, the chosen facts to be portrayed. The selected correspondence is also analyzed as part of building of this image. In the second chapter, the works of Eulália Sedeño Peres and Margaret W. Rossiter are used as reference to analyze both, the path followed by the scientist and her strategies. The attitudes and reactions of Mme. Curie, facing different situations and in different periods are analyzed in the scientist's correspondence with family and friends and other events in the life of the scientist that don t appear in the biography written by her daughter. The third chapter discusses the work of the scientist in the laboratory. The working conditions, the equipment developed by Pierre Curie, some factors that led the scientist to focus her studies on radioactive materials and the consequences of that choice. Moreover, facts reported are discussed in biography written by Eve Curie and others that were missing and could blacken her image. Thus, the analysis of the biography written by Eve Curie, other biographies and subsequent studies carried on the work of Mme Curie, show the importance of the biography for the History of the Science and the intent of the biographer to write about the history of a scientist